Predicting intention of mobile internet usage in Malaysia: extending the unified theory of acceptance and use of technology - Zendehdel, Marzieh; Paim, Laily (Taylor's Business School, Taylor's University, 2015)
The rapid advancement of innovation, and technology in mobile services, and the spread of smart devices have given greater significance to the use of mobile services for marketing researchers, consumers, and financial managers. In developing countries, such as Malaysia, mobile services play an important role but to the best knowledge of this researcher, studies in this area are rare, and this present study adds to the body of knowledge on mobile 4G user intentions by suggesting an innovative and comprehensive theoretical model that combines the Extended Unified Theory of Acceptance and Use of Technology (UTAUT) (Venkatesh, Thong, & Xu, 2012), with cultural moderators from Hofstede, providing new insights into factors affecting intention and how culture influences individual intention. This study used structural equation modeling (SEM), in a quantitative study conducted in an Asian region. Results revealed that the UTAUT model has a good data fit. The data indicate that performance expectancy, social influence and determination are the most significant factors of users’ decision to use the mobile internet (4G) service. As a determinant in the UTAUT model, there is also a significant moderating effect of individualism/collectivism fit. Moreover, collectivism/individualism was found to be the most significant cultural moderator of individual decisions to use the mobile internet (4G) service among Malaysian students.